Návrh revitalizace břehů zatopené pískovny Hulín - úsek1 - Skřečková, Kateřina (Vysoké učení technické v Brně. Fakulta stavební)
Cílem této bakalářské práce je posouzení současného stavu břehů zatopené štěrkopískovny v Hulíně a návrh vhodné biologické úpravy s vhodným vegetačním doprovodem. Upravovaný úsek se nachází v jižní části nádrže. Břehy jsou postihnuty abrazí, která je způsobena působením větrových vln a kolísáním hladiny.

The aim of this bachelor´s thesis is the assessment of the current state of the banks in a flooded the gravel reservoir in Hulín and design an appropriate biological stabilization with an appropriate bank vegetation. Adjusted section is in the southern part of the gravel pit. Banks are affected by abrasion, which is caused by the action of the waves and the level fluctuation.
Proposal to revitalize the banks of the flooded Hulín sandstones - section1
Keywords: abraze; stabilizace; nádrž; břehová čára; abrasion; stabilization; water reservoir; bank line